Two Important New Books (Academy of Management Journal, 1964)
The article reviews the books ?Basic Computer Programming: IBM 1620 FORTRAN,? by Decima M. Anderson and ?Industrial Relations: Management, Labor, and Society,? by W.V Owen and Howard V. Finston.